Assessing the impact of nocturia on health-related quality-of-life and utility: results of an observational survey in adults. (1st December 2016) - Andersson, Fredrik; Anderson, Peter; Holm-Larsen, Tove; Piercy, James; Everaert, Karel; Holbrook, Tim
Abstract: Background and aim: The impact of nocturia (getting up at night to void) on health-related quality-of-life (HRQoL) is often under-estimated. This study investigated the relative burden in terms of HRQoL and utilities of nocturia in a real-world setting. Methods: Patient data were collected from two surveys: a nocturia-specific, cross-sectional survey of physicians and their patients (DSP), and a general UK population health survey (HSFE). Utilities (EQ-5D-5L), productivity (Work Productivity and Activity Index), and the impact of nocturia symptoms (Nocturia Impact Diary and Overactive Bladder Questionnaires) were assessed against the number of voids. A robust linear regression model with propensity score weights was used to control for confounding factors in estimating utilities. Results: Physician-recorded data were available from 8, 738 patients across the US, Germany, Spain, France, and the UK; of these, 5, 335 (61%) included patient-reported outcomes. In total, 6, 302 controls were drawn from the two surveys and compared to 1, 104 nocturia patients. Deterioration of HRQoL was associated with increasing number of night-time voids ( p < 0.0001). In particular, significant differences were observed between 0–1 and ≥2 voids ( p < 0.001). The regression model demonstrated that nocturia (≥2 per night) is associated with a modest but significant deterioration in utility of 0.0134 ( p < 0.05). Limitations: The cause of nocturia is multifactorial and the mostly elderly patients may have several concomitant diseases. The authors tried to adjust for the most common ones, but there may be diseases or unknown relationships not included. Conclusions : Nocturia negatively affected HRQoL and patient utility. A clear effect is seen already at two voids per night. Every effort should, therefore, be made to reduce nocturia below the bother threshold of two voids per night.